2018
DOI: 10.1103/physrevlett.121.137401
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Hole Theory of the Effect of Quantum Nuclei on the X-Ray Absorption Spectra of Liquid Water

Abstract: Electron-hole excitation theory is used to unveil the role of nuclear quantum effects on the X-ray absorption spectral signatures of water, whose structure is computed via path-integral molecular dynamics with the MB-pol intermolecular potential model. Compared to spectra generated from the classically modeled water, quantum nuclei introduce important effects on the spectra in terms of both the energies and line shapes. Fluctuations due to delocalized protons influence the short-range ordering of the hydrogen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 68 publications
(84 reference statements)
2
53
0
Order By: Relevance
“…Combining these simulations with RPMD, thereby including NQEs, will be computationally very expensive but is not out of reach. That is, while RPMD simulations of water have been connected to various spectroscopic observables, such as IR (26)(27)(28) or X-ray absorption spectroscopy (58), they required the calculation of only a two-timepoint correlation function, as they simulated 1D responses. Converging a three-timepoint correlation function required for 2D Raman-THz spectroscopy will be computationally much more expensive, but efficient concepts to perform this task have already be proposed (59).…”
Section: Discussionmentioning
confidence: 99%
“…Combining these simulations with RPMD, thereby including NQEs, will be computationally very expensive but is not out of reach. That is, while RPMD simulations of water have been connected to various spectroscopic observables, such as IR (26)(27)(28) or X-ray absorption spectroscopy (58), they required the calculation of only a two-timepoint correlation function, as they simulated 1D responses. Converging a three-timepoint correlation function required for 2D Raman-THz spectroscopy will be computationally much more expensive, but efficient concepts to perform this task have already be proposed (59).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one may expect that the hybrid functional SCAN0 mitigates the self-interaction error in DFT, and brings the calculated IR spectra closer to the experiments. Furthermore, recent studies 42,46,47 suggested that nuclear quantum ef-fects due to light protons play a crucial role in obtaining accurate liquid water properties. The role played by quantum nuclei awaits the future investigation which is likely to broaden the spectral features and slightly reduce the frequencies of stretching band due to the delocalized protons.…”
Section: Discussionmentioning
confidence: 99%
“…53 More recently, molecular configurations extracted from classical and path-integral molecular dynamics simulations with MB-pol have been used in many-body perturbation theory calculations to model the X-ray absorption spectrum of liquid water as well as to determine the electron affinity of water, both in the bulk and at the air/water interface. 54,55 Building upon the demonstrated predictive power of MB-pol and taking advantage of the fact that isotope exchange is a rare event in computer simulations of water, which is completely turned off when using non-dissociable models, we present a systematic investigation of IR OH-stretch lineshapes calculated for different isotopic mixtures. Specifically, we report the results of centroid molecular dynamics (CMD) simulations for four different solutions: The combination of MB-pol, a water model exhibiting chemical and spectroscopic accuracy, with quantum dynamics simulations carried out within the CMD formalism allows for unambiguously disentangling intramolecular and intermolecular coupling effects on both the frequency shift and intensity of the OH-stretch lineshape in liquid water, which has so far remained elusive.…”
Section: Introductionmentioning
confidence: 99%